EVALUASI KINERJA SIMRS PADA TPPRJ RSD K.R.M.T WONGSONEGORO: ANALISIS DENGAN PENDEKATAN HOT-FIT UNTUK MENINGKATKAN EFEKTIVITAS PELAYANAN - Anastasia, Delvi; Setiono, Oki (VISIKES, 2025)
RSD K.R.M.T. Wongsonegoro has implemented a Hospital Management Information System (SIMRS) named SIWONGSO. Survey results indicate that patient blood type and ID number fields are often left unfilled in the system. Incomplete patient data may disrupt the filing process. The objective of this study was to evaluate the Hospital Management Information System at the Outpatient Registration of RSD K.R.M.T. Wongsonegoro using the HOT-FIT method. This research is descriptive and quantitative, with data collection through the HOT-FIT questionnaire. The study subjects were six outpatient registration officers at RSD K.R.M.T. Wongsonegoro, and the object of observation was the SIMRS display, technology, users, and organization within the Outpatient Registration section. The results showed that the outpatient registration data in SIMRS were generally complete. However, the layout size was insufficient, leading to an increased risk of data entry errors, and some patient ID numbers were incomplete. The technology component scored 4.26, indicating good performance; the human component scored 4.29, also rated as good; and the organizational component scored 4.16, which is also considered good. It is recommended that the hospital regularly evaluate the SIMRS implementation and provide training for the staff to improve their performance.